2021
DOI: 10.5194/essd-13-2777-2021
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Ocean Data Analysis Product in North America (CODAP-NA) – an internally consistent data product for discrete inorganic carbon, oxygen, and nutrients on the North American ocean margins

Abstract: Abstract. Internally consistent, quality-controlled (QC) data products play an important role in promoting regional-to-global research efforts to understand societal vulnerabilities to ocean acidification (OA). However, there are currently no such data products for the coastal ocean, where most of the OA-susceptible commercial and recreational fisheries and aquaculture industries are located. In this collaborative effort, we compiled, quality-controlled, and synthesized 2 decades of discrete measurements of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…Recent work has shown that observed amplitudes of seasonal pH and p CO 2 cycles increase moving landward from coastal ocean to nearshore and estuarine monitoring stations ( Fassbender et al, 2018 ). The dynamic seasonal cycles observed in the estuarine pH and p CO 2 monitoring data discussed here are consistent with this pattern, as well as with other published estuarine datasets (e.g., Hofmann et al, 2011 ; Wallace et al, 2014 ; Joesoef et al, 2015 ; Fairchild and Hales, 2021 ; Jiang et al, 2021 ; Torres et al, 2021 ). This highlights the relatively extreme carbonate chemistry experienced in estuaries compared to open ocean environments, and the continuing need to consider how ongoing coastal acidification will modify the seasonality of carbonate chemistry cycles ( Fassbender et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent work has shown that observed amplitudes of seasonal pH and p CO 2 cycles increase moving landward from coastal ocean to nearshore and estuarine monitoring stations ( Fassbender et al, 2018 ). The dynamic seasonal cycles observed in the estuarine pH and p CO 2 monitoring data discussed here are consistent with this pattern, as well as with other published estuarine datasets (e.g., Hofmann et al, 2011 ; Wallace et al, 2014 ; Joesoef et al, 2015 ; Fairchild and Hales, 2021 ; Jiang et al, 2021 ; Torres et al, 2021 ). This highlights the relatively extreme carbonate chemistry experienced in estuaries compared to open ocean environments, and the continuing need to consider how ongoing coastal acidification will modify the seasonality of carbonate chemistry cycles ( Fassbender et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…Strong seasonal variations in p CO 2 have been observed in other coastal systems (see Jiang et al, 2021 for a recent compilation of coastal data sets). For example, in the Delaware Bay, during the warmer summer months, p CO 2 values of ~400–500 μatm, have been recorded, with values reaching 200 to 350 μatm in the mid- and lower bay regions, while in the winter (December) p CO 2 measured across the bay ranged from 500–650 μatm ( Joesoef et al, 2015 ).…”
Section: Discussionmentioning
confidence: 78%
“…Our models include deep water in the MLR model, which makes it possible to be applied to other seasons. We used the coastal data product published by Jiang et al ( 2021 ) for the MAB and SAB regions ( except the GOMECC and ECOA cruises ) as an evaluation.…”
Section: Model Applicationsmentioning
confidence: 99%
“…The primary data product used to train these algorithms is the GLODAPv2.2020 data product update (Olsen et al 2020). In addition, we added data sets that will be included in the CARbon, tracer, and ancillary data In the MEDiterranean Sea (CARIMED) and that are included in the Coastal Ocean Data Analysis Project for North America (CODAP-NA; Jiang et al 2021) data products. These data from the Mediterranean Sea (46 cruises spanning from 1976 to 2018 and covering all the sub-basins in the Mediterranean Sea) and the Gulf of Mexico (three cruises spanning 2007 to 2012) are included to ensure these important regions are well-constrained and the cruise information is provided in Supporting Information S1.1.…”
Section: Data Products Training Data and Test Datamentioning
confidence: 99%
“…CODAP-NA(Jiang et al 2021) and ongoing CARIMED efforts (Supporting Information S1.1). The same lessons from the Sea of Japan/East Sea analysis apply to the reconstruction of measurements from the Gulf of Mexico and the Mediterranean Sea (Table11).…”
mentioning
confidence: 99%